Single‐cell sequencing reveals the features of adaptive immune responses in the liver of a mouse model of dengue fever - Yizhen Yuan; Qian Chen; Zhe Li; Fangzhou Cai; Dan Li; Wei Wang (Animal Models and Experimental Medicine)
Abstract Background Dengue fever, an acute insect‐borne infectious disease caused by the dengue virus (DENV), poses a great challenge to global public health. Hepatic involvement is the most common complication of severe dengue and is closely related to the occurrence and development of disease. However, the features of adaptive immune responses associated with liver injury in severe dengue are not clear. Methods We used single‐cell sequencing to examine the liver tissues of mild or severe dengue mice model to analyze the changes in immune response of T cells in the liver after dengue virus infection, and the immune interaction between macrophages and T cells. Flow cytometry was used to detect T cells and macrophages in mouse liver and blood to verify the single‐cell sequencing results. Results Our result showed CTLs were significantly activated in the severe liver injury group but the immune function‐related signal pathway was down‐regulated. The reason may be that the excessive immune response in the severe group at the late stage of DENV infection induces the polarization of macrophages into M2 type, and the macrophages then inhibit T cell immunity through the TGF‐β signaling pathway. In addition, the increased proportion of Treg cells suggested that Th17/Treg homeostasis was disrupted in the livers of severe liver injury mice. Conclusions In this study, single‐cell sequencing and flow cytometry revealed the characteristic changes of T cell immune response and the role of macrophages in the liver of severe dengue fever mice. Our study provides a better understanding of the pathogenesis of liver injury in dengue fever patients.